2021
DOI: 10.33275/1727-7485.2.2021.680
|View full text |Cite
|
Sign up to set email alerts
|

Immune factors and health of Antarctic explorers

Abstract: The immune system plays a major role in human homeostasis, yet a body’s unique individuality complicates the diagnostic forecasting of unfavourable physiological states and diseases. Studying the immunophenotypic features of winterers of the Ukrainian Antarctic Expeditions before, during, and after their assignments might shed some light on the possible place of immune accentuations in the development of certain physiological states. To determine the natural-killer (NK) cytotoxicity and the immunophenotype in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Misbalance results can lead to unfavorable conditions for pregnancy outcomes. Previously, we have shown that a similar misbalance in NK populations was also associated with an unfavorable health status during an Antarctic expedition [34]. Therefore, it is necessary to conduct a deeper and more detailed study of the physiological and phenotypic properties of different NKp46 populations.…”
Section: Discussionmentioning
confidence: 99%
“…Misbalance results can lead to unfavorable conditions for pregnancy outcomes. Previously, we have shown that a similar misbalance in NK populations was also associated with an unfavorable health status during an Antarctic expedition [34]. Therefore, it is necessary to conduct a deeper and more detailed study of the physiological and phenotypic properties of different NKp46 populations.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry was used for imunophenotype study (as shown in Zabara et al 2021). Peripheral blood was incubated with monoclonal antibodies labeled with FITC, PE, and PeCy5 according to the manufacturer's instructions (BD Biosciences, USA).…”
Section: Immunophenotyping Of Lymphocytes By Flow Cytometrymentioning
confidence: 99%
“…High levels of immune cell activation HLA-DR expression on T and NK cells is a factor of an unfavorable prognosis in reproduction [13,14] and similar levels are a factor of an unfavorable state of health during adaptation among participants of the Antarctic expedition [15]. But reduced activation of NK-lymphocytes may contribute to increased susceptibility to viral infections and bacterial complications [16].…”
Section: Introductionmentioning
confidence: 99%